Pembaharuan Pendidikan di Mesir : Analisis Terhadap Pemikiran Muhammad Abduh dan Pengaruhnya Terhadap Pembaharuan Pendidikan di Indonesia - Nazaruddin Lubis (Institut Agama Islam Al-Aziziyah Samalanga, 2023)
Muhammad Abduh is a reformer in the religious field, especially in the field of education. In the educational aspect he offers reforms in institutional aspects, curriculum and aspects of learning methods. At that time, such as stupidity and blind taqlid towards leadership. As for the efforts made by Muhammad Abduh aimed at awakening and changing people's mindsets from textual to contextual. His thoughts have brought major changes in the world of education in Egypt, including in Indonesia, this can be traced in the following article.